Women's artistic gymnastics coaches in Brazil: from opportunity to Olympic games. Issue 2 (2nd July 2016) - Carbinatto, Michele Viviene; Gamarano de Freitas, Elisangela; Dessupoio Chaves, Aline
Abstract: Utilising semi-structured interviews, this article examined the motives, the source of initial knowledge and the challenges faced by four high-performance women's artistic gymnastics coaches in Brazil. The results indicate that prior experience of the sport and related job opportunities were crucial for entry into the coaching profession. Additionally, although the coaches possessed degrees in physical education and sports, it was the community of practice and the sport-specific courses experienced that contributed most to their development. Finally, the biggest challenges faced by the coaches related to a search for professional recognition, only being seemingly linked to significant results such as a podium appearance at the Olympic Games.